Design of a compact silicon-based integrated passive band-pass filter with two tunable finite transmission zeros. (March 2016) - Pan, Jie; Wang, Huijuan; Tian, Gengxin; Cao, Liqiang; Yu, Daquan
Abstract: The thin film integrated passive device (IPD) has caused intensively attention due to its high integrated level and application in System in Package (SiP). Meanwhile, the IPD filter has shown great application value in modern wireless communication system. In this paper, the design method of a compact silicon-based lumped IPD band-pass filter with two tunable finite transmission zeros is shown. The passband of the designed filter is 2.4–2.5 GHz. Specific schematic is used to introduce two independently tunable transmission zeros. The specific schematic contains mutual inductor structure, which is realized by making two planar spiral inductors to partially overlap with each other and is helpful to decrease the size of the filter. The mutual inductance is adjustable by changing the overlap degree. To design and optimize the layout of the filter more efficiently, the schematic-layout mutual feedback method is presented. Finally, the measurement results verify the validity of the whole design process and method. The size of the designed second-order band-pass filter is 0.85 mm×0.85 mm×0.35 mm. To the best of our knowledge, the band-pass-filter developed in this paper has the smallest size while achieving equivalent electrical performance.